Dimensi Kemukjizatan Al-Qur’an (i‘jaz al-Qur’an) di Era Digital - Nur Uliah Awaliah. AR (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This article provides a comprehensive analysis of the Qur'an's miraculous nature (i'jaz al-Qur'an) through three main areas of discussion: the definition of i'jaz al-Qur'an, its various aspects, and its urgency for Muslims in the modern era. The theological foundation of this study is based on the verse of the Qur'an (Surah Al-Baqarah [2]: 23), which challenges humankind to produce even a single chapter comparable to the Qur'an—a challenge that remains unanswered to this day. This research employs a qualitative approach using the library research method, drawing upon classical sources such as the works of Al-Baqillani, Al-Jurjani, and Al-Zarqani, as well as contemporary studies by Faruq et al. (2024) and Nurkhatiqah et al. (2022). The findings reveal that the Qur'an's inimitability encompasses linguistic eloquence, legal perfection, scientific truth, and historical accuracy, all of which affirm that the Qur'an is divine revelation rather than human composition. Furthermore, this study highlights the urgency of understanding i'jaz al-Qur'an in the digital era, where Qur'anic verses are often decontextualized or misused. This article contributes to strengthening the epistemology of i'jaz interpretation as a response to religious misinformation in digital spaces, reaffirming the integration of revelation, reason, and knowledge in developing an authentic and rational Islamic intellectual tradition.